Pre-Omicron seroprevalence, seroconversion, and seroreversion of infection-induced SARS-CoV-2 antibodies among a cohort of children and teenagers in Montréal, Canada. (June 2023) - Zinszer, Kate; Charland, Katia; Pierce, Laura; Saucier, Adrien; McKinnon, Britt; Hamelin, Marie-Ève; Cheriet, Islem; Da Torre, Margot Barbosa; Carbonneau, Julie; Nguyen, Cat Tuong; De Serres, Gaston; Papenburg, Jesse; et al.
HIGHLIGHTS: We found high levels of seroreversion among the participating children. The median time to seroreversion was estimated at about 7.5 months. A total of 71% of infection-induced seroconversion were among the undetected infections. The risk of seroconversion was associated with different sociodemographic factors. ABSTRACT: Objectives: To use serological testing to assess the pre-Omicron seroprevalence, seroconversion, and seroreversion of infection-induced SARS-CoV-2 antibodies in children and adolescents in Montréal, Canada. Design: This analysis is from a prospective cohort study of children aged 2-17 years (at baseline) that included blood spots for antibody detection. The serostatus of participants was determined by enzyme-linked immunosorbent assays using the receptor-binding domain from the spike protein and the nucleocapsid protein as antigens. We estimated seroprevalence, seroconversion rates, and the likelihood of seroreversion at 6 months and 1 year. Results: The baseline (October 2020 to April 2021) seroprevalence was 5.8% (95% confidence interval [CI] 4.8-7.1), which increased to 10.5% (May to September 2021) and 11.0% (November 2021 to March 2022) for the respective follow-ups (95% CI 8.6-12.7; 95% CI 8.8-13.5). The crude rate of seroconversion over the study period was 12.8 per 100 person-years (95% CI 11.0-14.7). The adjusted hazard rates of seroconversion by child characteristics showed higher rates in children who were female, whose parent identified as a racial or ethnic minority, and in households with incomes in the lowest tercile of our study population. The likelihood of remaining seropositive at 6 months was 68% (95% CI 60-77%) and dropped to 42% (95% CI 32-56%) at 1 year. Conclusion: Serological studies continue to provide valuable contributions for infection prevalence estimates and help us better understand the dynamics of antibody levels after infection.